2018
DOI: 10.1001/jamaoncol.2017.4504
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Combined-Modality Therapy for Limited-Stage Small Cell Lung Cancer

Abstract: Substantial proportions of patients documented in a major US cancer registry did not receive radiation therapy or chemotherapy as part of initial treatment for limited-stage SCLC, which, in turn, was associated with poor survival. Lack of radiation therapy delivery was uniquely associated with government insurance coverage, suggesting a need for targeted access improvement in this population. Additional work will be necessary to conclusively define exact population patterns, specific treatment deficiencies, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 15 publications
6
52
0
Order By: Relevance
“…More specifically, patients with nonsquamous NSCLC with Medicaid/other public or no insurance were less likely to receive bevacizumab, whereas patients with Medicaid/other public or military-related insurance were less likely to receive TKIs. Our findings are consistent with studies that have noted that Medicaid and uninsured patients with NSCLC and other cancers are less likely to receive recommended treatments than patients with private insurance (20,(31)(32)(33)(34). Our findings also are consistent with two studies that found fewer patients with NSCLC with public insurance received molecular testing or TKIs compared with patients with private insurance (9,35).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More specifically, patients with nonsquamous NSCLC with Medicaid/other public or no insurance were less likely to receive bevacizumab, whereas patients with Medicaid/other public or military-related insurance were less likely to receive TKIs. Our findings are consistent with studies that have noted that Medicaid and uninsured patients with NSCLC and other cancers are less likely to receive recommended treatments than patients with private insurance (20,(31)(32)(33)(34). Our findings also are consistent with two studies that found fewer patients with NSCLC with public insurance received molecular testing or TKIs compared with patients with private insurance (9,35).…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that patients with Medicaid insurance or no insurance are less likely to receive recommended cancer treatments than patients with private insurance (16)(17)(18). Compared to patients with private insurance, patients with lung cancer with no insurance or public insurance have higher mortality, more treatment delays, and are less likely to receive molecular testing, chemotherapy, or radiation (9,(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Although some patients may prefer to undergo a complex surgical procedure at a local LVH, 41 there is concern that socioeconomic barriers may prevent many patients from accessing care at HVHs and specialized referral centers. 20,42,43 In the current study, demographic data available in the NCDB suggest that patients who underwent surgery at LVHs may be of lower socioeconomic status, raising concerns that socioeconomic circumstances may be barriers to a patient's ability to access care at HVHs for the treatment of RPS.…”
Section: Total Number Of Primary Rps Surgical Resections Versus % Of mentioning
confidence: 81%
“…In the real world, the treatment plan depended on several factors, such as patients' and physicians' discretions, patients' ECOG performance status, and waiting time to receive each treatment. For instance, in the United States, only 55% of patients with LS received combined-modality therapy, which was limited by the health insurance system, resulting in poorer survival [16].…”
Section: Discussionmentioning
confidence: 99%
“…Median survival time (MST) of SCLC patients in Phase III trials with LS and ES was 17 to 30 months and 7.1 to 12.8 months, respectively [6]- [14]. In the real world, previous reports revealed that the survival of SCLC patients with LS and ES was 10.3 to 18.2 months and 5.5 to 10.2 months, respectively [15] [16] [17].…”
Section: Introductionmentioning
confidence: 99%